2009
DOI: 10.1007/s10683-009-9224-x
|View full text |Cite
|
Sign up to set email alerts
|

How certain is the uncertainty effect?

Abstract: We replicate three tasks for which Gneezy, List and Wu (Q. J. Econ. 121(4): 2006) document the so-called uncertainty effect: People value a binary lottery over non-monetary outcomes less than other people value the lottery's worse outcome. While the authors implement verbal lottery descriptions, we use a physical lottery format and also provide subjects with complete information about the goods they are to value. We observe for all three pricing tasks that subjects' willingness to pay for the lottery is signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Keren and Willemsen () and Rydval et al . () found that the uncertainty effect as reported in Gneezy et al . () may be a result of task framing ambiguity of experimental instructions.…”
supporting
confidence: 58%
“…Keren and Willemsen () and Rydval et al . () found that the uncertainty effect as reported in Gneezy et al . () may be a result of task framing ambiguity of experimental instructions.…”
supporting
confidence: 58%
“…Rydval et al (2009), in contrast, do not find any uncertainty effects in their experiment.-181 -© 2018 Japanese Economic Association C. Nuryakin and A. Munro: Investigating the Economics of Fukubukuro…”
mentioning
confidence: 90%
“…Several recent studies have re‐examined the uncertainty effect in different situations. Some of them found evidence for the existence of an uncertainty effect (Sonsino, 2008; Simonsohn, 2009), while others provide empirical evidence that casts serious doubts on its existence, concluding that this phenomenon is less robust than GLW's results suggest (Ortmann et al , 2007; Keren and Willemsen, 2009; Rydval et al , 2009). For example, researchers have raised the possibility that GLW's findings were caused by participants’ misunderstanding of the lottery (Ortmann et al , 2007; Keren and Willemsen, 2009; Rydval et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them found evidence for the existence of an uncertainty effect (Sonsino, 2008; Simonsohn, 2009), while others provide empirical evidence that casts serious doubts on its existence, concluding that this phenomenon is less robust than GLW's results suggest (Ortmann et al , 2007; Keren and Willemsen, 2009; Rydval et al , 2009). For example, researchers have raised the possibility that GLW's findings were caused by participants’ misunderstanding of the lottery (Ortmann et al , 2007; Keren and Willemsen, 2009; Rydval et al , 2009). In order to increase the transparency of the lottery structure, Rydval et al (2009) replicate GLW experiments using a ‘physical’ format: subjects state their willingness‐to‐pay (WTP) for the opportunity of drawing a good (a gift certificate or a deferred payment form) from a closed bag containing two goods that are identical except for their face value.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation